2012
DOI: 10.1128/jvi.05811-11
|View full text |Cite
|
Sign up to set email alerts
|

RING Domain Mutations Uncouple TRIM5α Restriction of HIV-1 from Inhibition of Reverse Transcription and Acceleration of Uncoating

Abstract: Rhesus TRIM5␣ (TRIM5␣ rh ) is a cytosolic protein that potently restricts HIV-1 at an early postentry stage, prior to reverse transcription. The ability of TRIM5␣ rh to block HIV-1 infection has been correlated with a decrease of pelletable HIV-1 capsid during infection. To genetically dissect the ability of TRIM5␣ to block reverse transcription, we studied a set of TRIM5␣ rh RING domain mutants that potently restrict HIV-1 but allow the occurrence of reverse transcription. These TRIM5␣ rh RING variants blocke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
76
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 60 publications
(113 reference statements)
5
76
0
Order By: Relevance
“…Viral capsids are thought to shield incoming retroviral replication complexes from cellular sensors of infection. The t 1/2 for MLV attachment through completion of reverse transcription is ∼3-4 h (41), and capsid disassembly is believed to occur either simultaneously with or just before reverse transcription (42,43). Thus, the less stable glyco-Gag mutant capsid could allow intracellular sensors to more readily sense viral RNA or DNA.…”
Section: Apobec3 Restricts Endogenous Reverse Transcription Of Glyco-gagmentioning
confidence: 99%
“…Viral capsids are thought to shield incoming retroviral replication complexes from cellular sensors of infection. The t 1/2 for MLV attachment through completion of reverse transcription is ∼3-4 h (41), and capsid disassembly is believed to occur either simultaneously with or just before reverse transcription (42,43). Thus, the less stable glyco-Gag mutant capsid could allow intracellular sensors to more readily sense viral RNA or DNA.…”
Section: Apobec3 Restricts Endogenous Reverse Transcription Of Glyco-gagmentioning
confidence: 99%
“…In the second step, TRIM5␣ induces the abortive disassembly of the viral capsid core and prevents the accumulation of reverse transcription (RT) products. The latter step requires the E3 ligase activity of the TRIM5␣ RING domain and is sensitive to proteasome inhibitors, although restriction of infection remains potent in both cases (9,(21)(22)(23)(24). Additionally, the presence of restriction-sensitive virus triggers the degradation of TRIM5␣, and this degradation is also sensitive to proteasome inhibitors (25).…”
mentioning
confidence: 99%
“…Numerous studies have found that retroviral restriction by TRIM5␣ proteins occurs by a two-step mechanism (21)(22)(23)(24)(25). In the first step, which is sufficient to prevent infection, TRIM5␣ recognizes the viral capsid via its C-terminal PRY/SPRY domain (or CypA in the case of TRIM-Cyp).…”
mentioning
confidence: 99%
“…As shown in Figure 2B, BI-2 and PF74 did not affect the stability of the HIV-1 core bearing the change T107N. These results suggested that the ability , and used to perform the fate of the capsid assay 12 hours post-infection, as described [9,11]. Briefly, HIV-1 infected cells were used to prepare post-nuclear supernatants that were layered onto a 50% sucrose cushion to separate soluble from pelletable HIV-1 capsids.…”
Section: Bi-2 Destabilizes the Hiv-1 Core During Infectionmentioning
confidence: 99%
“…For this purpose, we challenged Cf2Th cells with HIV-1-GFP in the presence of 50 μM BI-2 and performed the fate of the capsid 12 hours post-infection, as previously described [9][10][11]. As shown in Figure 2A, the use of BI-2 destabilized the HIV-1 core during infection when compared with the DMSO control.…”
Section: Bi-2 Destabilizes the Hiv-1 Core During Infectionmentioning
confidence: 99%